Apport Du SIG Et De L’analyse Multicritère Dans La Prospection Hydrogéologique Du Socle Précambrien De Gagnoa (Centre-Ouest De La Côte d’Ivoire) - Onétié Zahibo Oscar; Lasm Théophile; Coulibaly Adama; Baka Derving; Fossou N’guessan Marie Rosine; Youan Ta Marc; Yao Kouadio Assemien François; Aoulou Kouassi Aristide (European Scientific Journal, ESJ, 2016)
Côte d’Ivoire is constituted in more than 97.5% of crystalline basement which contains the main part of groundwater resources of the country. These resources are contained in the weathering material and fissured aquifers. Gagnoa area located at the Central West of Côte d'Ivoire, on crystalline and metamorphic basement. In this area, surface water and groundwater are exploited for the water supply of the populations. However surface water are often doubtful quality and can affect the health of these populations. Thus find water resources in sufficient and good quality amount is a necessity in this area. The study aims to identify favourable areas for the archievement of drillings with important discharge using geomorphologic, hydrogeological data and remote sensing. Multi-criteria analisys methods were used in this study. The database is constituted by various data in particular, data sheets of drillings, hydroclimatic statements and satellite image. This database was stored, analyzed, treated and managed using ARCGIS 10.2. software. Various treatments allowed to establish various thematic maps (accessibility, exploitability, availability). The synthesis of all information inside a SIG allowed to establish the maps of favourable areas to achieve drillings with large discharges. The classes of good and excellent sensibility cover 26% of the study area. These favourable areas for the achievement of drillings with important discharge are located at the center and south of the study area. Validation of this map showed that 66% of the water points (drillings) with discharge superior to 5 m3/h overlap on the good and excellent classes of sensibility. The various zones of productivity of Gagnoa area were able to be characterized. These results are very interesting and useful for the hydrogeological prospecting. They contribute to a better knowledge and a groundwater resource management.